Introducing ultra-high-pressure low-salt-rejection reverse osmosis for energy-efficient concentration of industrial brines - Yuliya Schiesser; Christine Kleffner; Jochen Henkel; Herbert Bassek; Eric Kadaj; Angel Abajas; Gerd Braun (Water Resources and Industry, 2025)
This study demonstrated a novel membrane-based process consisting of Ultra-High-Pressure Reverse Osmosis (UHPRO) and Ultra-High-Pressure Low-Salt Rejection Reverse Osmosis (UHP-LSRRO) at 120 bar, combined with energy recovery technology in the context of brine concentration. Basic assessment of energy demand and efficiency analysis were done based on experimental investigations using available industrial-scale equipment to facilitate accelerated industrial implementation, including the application-specific performance of the 4-inch membrane elements and the energy recovery device.With the membrane module prototype in this study, a maximum NaCl concentration of around 170 g/L was determined while the flux remained higher than 3.5 L/m2h. A simple and robust plant design combining UHPRO and UHP-LSRRO was proposed, and the integration of energy recovery was considered. A comparative energy consumption analysis revealed that the process achieved an approximate 45 % reduction in energy demand relative to Mechanical Vapor Compression (MVC) systems when concentrating sodium chloride solutions from initial concentrations of 65 g/L to final concentrations of 300 g/L.